The Influence of Technological Progress, Understanding, Motivation, And Investment Risk on The Investment Interest of Students in Yogyakarta - Lestari Yuli Prastyatini, Sri; Krisantus Ratu Lele Muda, Tobias (Dinasti International Journal of Economics, Finance & Accounting, 2024)
This study aims to prove the effect of technological progress, understanding, motivation, and investment risk on student investment interest in Yogyakarta. This research is focused on economics faculty students in Yogyakarta in 2019-2021. The sampling technique used in this study was convenience sampling with the number of respondents obtained as many as 110 respondents. The data analysis technique uses multiple linear regression. The data obtained in this study were collected by distributing questionnaires via google form. The results of the analysis show that technological progress and investment motivation have a positive effect on student investment interest. Investment understanding has no effect on student investment interest and investment risk has a negative effect on student investment interest.